Efficacy of natural and synthetic inhibitors in the elimination of viruses in potato (Solanum tuberosum L.) - E. V. Shishchenko; I. V. Kim; E. N. Barsukova; I. M. Yermak; A. O. Kravchenko; A. G. Klykov (Труды по прикладной ботанике, генетике и селекции)
Background. Developing new effective plant protection methods against viruses is a vital task for seed potato production. The use of virus inhibitors (mainly synthetic ones) is the most common method in potato virus control. Products of natural origin might be a way to reduce the dependence on synthetic inhibitors. Among the former, extracts from seaweeds have high potential, producing a low or no negative impact on the environment or human health. Materials and methods. The materials of the research included potato cvs. ‘Poseidon’ and ‘Orion’ developed at the Federal Scientific Center of Agricultural Biotechnology of the Far East named after A.K. Chaika, the commercial antiviral product Ribavirin, and the sulfated polysaccharide – carrageenan – obtained from red algae at the G.B. Elyakov Pacific Institute of Bioorganic Chemistry. A highly sensitive PCR method was employed to detect viral infections in plant samples. Results. The efficacy of chemotherapy with Ribavirin (0.03%) was established at 79.8% against PVY, 77.0% against PLRV, 80.3% against PVM, and 84.5% against PVS. The most successfully eliminated viruses were PVY, PVM, and PVS. Carrageenan as an antiviral substance eliminated potato viruses at the following rates: PLRV in 74.7% of the explants, PVM in 70.2%, PVS in 69.2%, and PVY in 16.9%. Conclusion. Analyzing the antiviral activity of natural and synthetic virus inhibitors in the case study of carrageenan and Ribavirin demonstrated their high efficacy against potato viruses. Natural polysaccharides – carrageenans – were observed to have a significant antiviral effect, so their use in agricultural biotechnology might be promising for new experiments. Our approach successfully eliminated viruses in two new promising potato cultivars, ‘Poseidon’ and ‘Orion’, which were included in the system of virus-free seed production. These cultivars were submitted for patenting and official testing under the State Variety Trials.